Analysis of the Impact of the Ajman Free Zone Employee Services on the Level of Customers Satisfaction - Solanki, Kalpana (Archives of Business Research, 2022)
This research paper focuses on the impact of Ajman free zone employee’s performance on customer satisfaction and the challenges they might face in achieving both of customers and investors satisfaction. The main goal of the research paper is to analyse the role of Ajman free zone work practices and their employee’s performance on customers satisfaction which leads to retaining loyal customers. The literature review focus on articles related to service industry and its impact of customer services. The data collection in this research paper is done using primary method and secondary method. In primary data collection method interviews with Ajman free zone employees and surveys that were completed by approximately 40 customer of Ajman free zone customers were used .The secondary data collection method included -sources from internet and peer-reviewed journals and articles.